Early changes in adipokines from overweight to obesity in children and adolescents - Rafael Machado Mantovani; Natália Pessoa Rocha; Daniel Massote Magalhães; Izabela Guimarães Barbosa; Antônio Lúcio Teixeira; Ana Cristina Simões e Silva (Elsevier, 2016)
Objective: Childhood obesity has been associated with metabolic syndrome and cardiovascular diseases. This study aimed to compare plasma levels of traditional metabolic markers, adipokines and soluble tumor necrosis factor receptor type 1 (sTNFR1) in overweight, obese and lean children. We also assessed the relationships of these molecules with classical metabolic risk factors. Methods: This study included 104 children and adolescents, which were grouped as: lean (n = 24), overweight (n = 30), and obese subjects (n = 50). They were subjected to anthropometrical, clinical and laboratorial measurements. All measurements were compared between groups. Correlation analyses were also performed to evaluate the association between clinical data, traditional metabolic markers, adipokines and sTNFR1. Results: Fasting glucose, insulin, homeostatic model assessment of insulin resistance (HOMA-IR), LDL-cholesterol and triglycerides were comparable in lean, overweight and obese subjects. Plasma levels of sTNFR1 were similar in lean and overweight subjects, but significantly increased in obese group. Leptin, adiponectin and resistin levels did not differ when overweight were compared to obese subjects. However, all adipokines differed significantly when lean subjects were compared to overweight and obese individuals. Plasma levels of adiponectin were negatively correlated with body mass index (BMI), whereas leptin, resistin and sTNFR1 concentrations positively correlated with BMI. Conclusion: Our results showed significant differences in circulating levels of the evaluated markers when lean, overweight and obese individuals were compared, suggesting that these biomarkers may change from lean to overweight and from overweight to obesity. Resumo: Objetivo: A obesidade na infância tem sido associada à síndrome metabólica e a doenças cardiovasculares. O objetivo deste estudo foi comparar níveis plasmáticos de marcadores metabólicos tradicionais, adipocinas e do receptor solúvel de fator de necrose tumoral tipo 1 (sTNFR1) em crianças com sobrepeso, obesas e magras. Também avaliamos as relações dessas moléculas com fatores de risco metabólico clássicos. Métodos: Este estudo incluiu 104 crianças e adolescentes, agrupados da seguinte forma: indivíduos magros (n = 24), com sobrepeso (n = 30) e obesos (n = 50). Eles foram submetidos a medições antropométricas, clínicas e laboratoriais. Todas as medições foram comparadas entre os grupos. Também foram realizadas análises de correlação para avaliar a associação entre dados clínicos, marcadores metabólicos tradicionais, adipocinas e sTNFR1. Resultados: Glicemia de jejum, insulina, modelo de avaliação da homeostase da resistência à insulina (HOMA-IR), colesterol LDL e triglicerídeos foram comparáveis em indivíduos magros, com sobrepeso e obesos. Os níveis plasmáticos de sTNFR1 foram similares em indivíduos magros e com sobrepeso, porém significativamente maiores no grupo obeso. Os níveis de leptina, adiponectina e resistina não diferiram quando indivíduos com sobrepeso foram comparados aos obesos. Contudo, todas as adipocinas diferiram significativamente quando indivíduos magros foram comparados a indivíduos com sobrepeso e obesos. Os níveis plasmáticos de adiponectina estavam negativamente correlacionados ao índice de massa corporal (IMC), ao passo que as concentrações de leptina, resistina e sTNFR1 estavam positivamente correlacionadas ao IMC. Conclusão: Nossos resultados mostraram diferenças significativas nos níveis circulantes dos marcadores avaliados ao comparar indivíduos magros, com sobrepeso e obesos, sugerindo que esses biomarcadores poderão mudar de indivíduos magros para indivíduos com sobrepeso e de indivíduos com sobrepeso para obesos. Keywords: Leptin, Adiponectin, Resistin, Metabolic markers, Soluble tumor necrosis factor receptor, Palavras-chave: Leptina, Adiponectina, Resistina, Marcadores metabólicos, Receptor solúvel de fator de necrose tumoral